2016
DOI: 10.5539/elt.v9n8p53
|View full text |Cite
|
Sign up to set email alerts
|

Facebook Activities and the Investment of L2 Learners

Abstract: <p>The article discusses the investment of L2 learners in the English language on Facebook that they portrayed through their Facebook activities. It studied four informants consisted of diploma students in a Malaysian university. The study consisted of 14 weeks of online observation and semi-structured interviews. Data were collected from online observation and semi-structured interviews. Data were analysed using thematic analysis and Second Cycle Coding. The findings revealed that there were five Facebo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…writing comments, quotes, games, songs, cooking, and singers), and interpersonal and intergroup communication. The findings are similar to the results of Shafie et al (2016) in that language learners participated in Facebook activities: writing comments, reading news feeds, and joining in closed-group activities. They also correspond to Chang (2020), who revealed that learner autonomy is linked to students' motivation and their awareness of potential learning challenges.…”
Section: Discussionsupporting
confidence: 84%
“…writing comments, quotes, games, songs, cooking, and singers), and interpersonal and intergroup communication. The findings are similar to the results of Shafie et al (2016) in that language learners participated in Facebook activities: writing comments, reading news feeds, and joining in closed-group activities. They also correspond to Chang (2020), who revealed that learner autonomy is linked to students' motivation and their awareness of potential learning challenges.…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, Gamble and Wilkins (2014) [75] supported that students' attitudes towards Presentational Communication are highly positive. Likewise, Shafie, Yaacob, & Karpal Singh (2016) [45] validated that posting writing in English on Facebook was the most favorite activity among students.…”
Section: Presentational Communicationmentioning
confidence: 96%
“…At the end of the 11week teaching process, expository text comprehension skills of the experimental-group students who implemented reciprocal-teaching strategy were developed at a statistically significant level. Shafie, Yaacob & Singh (2016) examined Facebook activities of L2 learners in the English language. Participants were four diploma students who were active Facebook users.…”
Section: ‫وﻳﺐ‬ ‫ﻋﻠﻰ‬ ‫ﻗﺎﺋﻢ‬mentioning
confidence: 99%